1994
DOI: 10.1103/physrevb.50.6792
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ordering inU2Pd2In andet al.

Abstract: Magnetic ordering in U2Pd2Sn and U2Pd2InPurwanto, A.; Robinson, R.A.; Havela, L.; Sechovsky, V.; Svoboda, P.; Nakotte, H.; Prokes, K.; de Boer, F.R.; Seret, A.; Winand, J.M.; Rebizant, J.; Spirlet, J.C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 13 publications
2
25
0
1
Order By: Relevance
“…6 If the anisotropy were driven by hybridization-mediated f -f coupling only, one would anticipate a moment configuration perpendicular to the shortest U-U distance in all cases ͑similar to the findings in UTX compounds͒. While this was found to be true in U 2 Pd 2 X compounds, 23 the case of U 2 Ni 2 Sn seems to contradict this rule. 24 As an aside, we note that very recent bandstructure calculations including spin-orbit coupling have reproduced the experimentally observed noncollinear antiferromagnetic structure in U 2 Pd 2 Sn, and it was shown that this structure is energetically preferred over the other possible moment arrangements.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…6 If the anisotropy were driven by hybridization-mediated f -f coupling only, one would anticipate a moment configuration perpendicular to the shortest U-U distance in all cases ͑similar to the findings in UTX compounds͒. While this was found to be true in U 2 Pd 2 X compounds, 23 the case of U 2 Ni 2 Sn seems to contradict this rule. 24 As an aside, we note that very recent bandstructure calculations including spin-orbit coupling have reproduced the experimentally observed noncollinear antiferromagnetic structure in U 2 Pd 2 Sn, and it was shown that this structure is energetically preferred over the other possible moment arrangements.…”
Section: Introductionmentioning
confidence: 65%
“…We find no evidence for a crossover in the temperature dependences of d ʈ and d Ќ , as was reported for U 2 Pd 2 Sn. 23 …”
Section: Crystal Structurementioning
confidence: 99%
“…Neutron powder diffraction experiments at LANSCE, Los Alamos, have indicated that in UzPd21n and U2Pd2Sn the same non-collinear ordering exists with U moments 0304-8853/95/$09.50 © 1995 Elsevier Science B.V. All rights reserved SSDI 0304-8853(94)00934-1 lying within the basal plane along the directions of the [1 1 0] type [3]. The magnetic and crystallographic unit cells are identical.…”
mentioning
confidence: 95%
“…The R 2 T 2 X compounds, with R = Rare-Earth or Uranium, T = Fe, Co, Ni, Ru, Rh or Pd and X = Sn or In, crystallise in the tetragonal U 3 Si 2 -type crystal structure with space group P 4/mbm [30][31][32][33][34][35]. The occupied Wyckoff positions are (4h) R: (x R , 1/2 + x R , ); (4g) T: (x T , 1/2 + x T , 0) and X: (2a) (0, 0, 0).…”
Section: Symmetry Analysis Of the Commensurate Magnetic Structures Ofmentioning
confidence: 99%
“…The full representations of the space group Immm are two dimensional and can be constructed by using the induction formula (30). As an example of the use of formula (30) we give below the 2D matrix corresponding to the operator 2 y for irrep 3 :…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%